IDENTITAS DAN GERAKAN SOSIAL DI RUMPIN - Gilang Ramadhan (JURNAL POLINTER : KAJIAN POLITIK DAN HUBUNGAN INTERNASIONAL, 2018)
The social movement cannot automatically come to the surface without the presence of anignition, one of the most attractive ignitions is the success story of another movement which is the reference group of a socially alienated society with the State. Identity then emerges as a means of binding of the movement so that the movement can have the spirit to rise from alienation and have the power to fight its rivals. This paper takes a case study of Rumpin farmers' resistance in Bogor over their land over functions by the Indonesian Air Force. The conclusion of this paper is that the presence of a one-sided reference group can lead to the spirit to be able to resist the rival movement if the reference group has an identity equivalent to them, but it would be disastrous to take the wrong reference group that is used as a reference in the movement because by itself the identity of the movement becomes blurred and also including the loss of the direction of the substance of a movement.